2016
DOI: 10.4070/kcj.2016.46.2.229
|View full text |Cite
|
Sign up to set email alerts
|

White Blood Cell Count to Mean Platelet Volume Ratio Is a Prognostic Factor in Patients with Non-ST Elevation Acute Coronary Syndrome with or without Metabolic Syndrome

Abstract: Background and ObjectivesLeukocyte and platelet have been found to be associated with metabolic syndrome (MetS). We aimed to determine the usefulness of a novel marker named white blood cell count to mean platelet volume ratio (WMR) for predicting outcomes of non-ST elevation acute coronary syndrome (NSTE-ACS) with or without MetS.Subjects and MethodsA total of 331 NSTE-ACS individuals (60±12.5 years, 57.4% male) were enrolled and followed for a median of 24 months. MetS was identified using the National Chole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…It was estimated that about 40% of cases of preterm birth have been correlated with intrauterine infection . Infection induced inflammatory condition that involves the recruitment of leukocytes, including neutrophils, monocytes, and lymphocytes; thus, increased number of immune cells in the peripheral blood may indicate the progress of the infectious disease . In the present study, the neutrophil count and WBC count of control, non‐HCA patients, and HCA patients were compared.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It was estimated that about 40% of cases of preterm birth have been correlated with intrauterine infection . Infection induced inflammatory condition that involves the recruitment of leukocytes, including neutrophils, monocytes, and lymphocytes; thus, increased number of immune cells in the peripheral blood may indicate the progress of the infectious disease . In the present study, the neutrophil count and WBC count of control, non‐HCA patients, and HCA patients were compared.…”
Section: Discussionmentioning
confidence: 95%
“…Some previous studies demonstrated that neutrophil‐to‐lymphocyte ratio of the patients was associated with the diagnosis and outcome of different diseases, including acute cerebrovascular diseases . On the other hand, the neutrophil‐to‐white blood cell ratio (NE/WBC) or platelet‐to‐white blood cell ratio (PLT/WBC) was significantly increased in patients with different type of diseases, for example, cancer, cardiovascular disease, and autoimmune diseases, suggesting that either NE/WBC or PLT/WBC may serve as novel biomarkers for the early diagnosis of those diseases …”
Section: Introductionmentioning
confidence: 99%
“…The metabolic syndrome (MetS) is a cluster of major cardiovascular risk factors including fasting hyperglycemia, hypertriglyceridemia, low high‐density lipoprotein, abdominal obesity, and systemic arterial hypertension . Among its diagnostic criteria, those of the National Cholesterol Education Program Adult Treatment Panel III (NCEP‐ATP III) are the most often used .…”
Section: Introductionmentioning
confidence: 99%
“…All these novel biomarkers are inflammation-based and have been useful in diagnosing other inflammatory diseases. White blood cell to mean platelet volume ratio is another novel biomarker examined in coronary artery disease and metabolic syndrome,19,20 which may be useful to detect the presence of CSFP as well.…”
mentioning
confidence: 99%